Restoring mitochondrial quantity and quality to reverse the Warburg effect and drive neuroblastoma differentiation - Haowen Jiang; Sarah Jane Tiche; Clifford Jiajun He; Junyan Liu; Fuyun Bian; Mohamed Jedoui; Balint Forgo; Md Tauhidul Islam; Meng Zhao; Pamela Emengo; Bo He; Yang Li; et al. (Proceedings of the National Academy of Sciences, 2025)
Reduced mitochondrial quality and quantity in tumors is associated with dedifferentiation and increased malignancy. However, it remains unclear how to restore mitochondrial quantity and quality in tumors and whether mitochondrial restoration can drive tumor differentiation. Our study shows that restoring mitochondrial function using retinoic acid (RA) to boost mitochondrial biogenesis and a mitochondrial uncoupler to enhance respiration synergistically drives neuroblastoma differentiation and inhibits proliferation. U- 13 C-glucose/glutamine isotope tracing revealed a metabolic shift from the pentose phosphate pathway to oxidative phosphorylation, accelerating the tricarboxylic acid cycle and switching substrate preference from glutamine to glucose. These effects were abolished by electron transport chain (ETC) inhibitors or in ρ 0 cells lacking mitochondrial DNA, emphasizing the necessity of mitochondrial function for differentiation. Dietary RA and uncoupler treatment promoted tumor differentiation in an orthotopic neuroblastoma xenograft model, evidenced by neuropil production and Schwann cell recruitment. Single-cell RNA sequencing of xenografts revealed that this strategy effectively eliminated the stem cell population, promoted differentiation, and increased mitochondrial gene signatures along the differentiation trajectory, potentially improving patient outcomes. Collectively, our findings establish a mitochondria-centric therapeutic strategy for inducing tumor differentiation, suggesting that maintaining/driving differentiation in tumor requires not only ATP production but also continuous ATP consumption and sustained ETC activity.